Az impériumváltás hatása a felekezeti viszonyok alakulására a szerbiai Bánságban - Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2010)
The part of Banovina (Banat) which was annexed to the Kingdom of Serbs, Croats and Slovenes by the Treaty of Trianon covers 9,776 km². This summary is restricted to the religious history of this part which can be called the Serbian Banat (srbski Banat) although it is obvious that this territory used to form an organic unit until the division after the First World War, so it is not reasonable to discuss separately the so-called Serbian Banovina covering 9,776 square kilometers when dealing with the history of Banovina before 1920. The reason of laying greater emphasis on the Catholic Church is that the majority of Hungarians living in the territory belong to this denomination. Already between the Two World Wars the rate of Serbian population started to grow significantly, which was the result of immigration from other parts of the Kingdom of Serbs, Croats and Slovenes, the later Yugoslavia. The practical implementation of ecclesiastical reforms also served the enhancement of the Slavic ethnical influence of the majority of the new state. The lead of the apostolic government of Banat created from the territory of the diocese of Csanád annexed to the Kingdom of Serbs, Croats and Slovenes was taken by a prelate of Croatian origin although the vast majority of the believers were of Hungarian and German origin. By the fact that the new power did not acknowledge the justification of denominational schools, the Hungarian church education was gradually being eliminated. The ethnical and political changes following World War II, the deportation of Germans, and the waves of violence against Hungarians all influenced the religious affairs of the area. The number of Catholic believers decreased to one half and from the aspect of nationalities there was a radical change in the Catholic Church: the community mainly consisting of German and Hungarian believers became a „Hungarian ecclesia”. The main purpose of this study is to point out the significant national and at the same time ecclesiastical reforms that took place in the area in the past ninety years.